Re-Imagining the Role of Female Players in the Making and Restoring of the UHADI Musical Bow - Pepu, Lindelwa (Arts Research Africa, 2022)
This paper, written from an African feminist perspective, focuses on the uhadi musical bow, a historical instrument found in museums, particularly in Museum Africa in Johannesburg. The mislabelling and lack of contextual information about the uhadi bow in the museum collection hinder the understanding of its origin and the recognition of its makers. The research highlights the role of women as the likely original makers and performers of the uhadi bow. It explores the unique features, construction, and playing techniques of the instrument. The study also profiles female uhadi players, emphasising their contribution to reviving and preserving the instrument’s cultural significance.